Analisis Eksperimental Sistem Kelistrikan Body pada Motor Honda Supra Fit New 2006 - Dewa Nyoman Susilayasa; Nurhidayati Nurhidayati; Kasum Kasum; Dadang Rustandi; Yusuf Maulana (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2026)
The body electrical system of the Honda Supra Fit New 2006 supports lighting, signaling, charging, and riding safety. In vehicles with long service life, wiring and connection faults can reduce system reliability. This study aimed to analyze the condition of the body electrical system, diagnose the source of faults, conduct repairs, and evaluate system performance after repair. An experimental method was applied to one Honda Supra Fit New 2006 through visual inspection, circuit checks, multimeter measurements, replacement of damaged components, functional testing, and a road test. The initial inspection identified worn and peeled body wiring, several loose connections, a lamp socket deformed by heat, and non-functioning headlamp and brake lamp due to a short circuit. Repairs included replacing one complete body wiring set, the headlamp, and the brake lamp, followed by rearrangement and rechecking of the wiring connections. After repair, battery voltage was 12.6 V with the engine off and 13.9 V with the engine running. The headlamp, brake lamp, turn signals, horn, panel indicators, and grounding operated normally. These results show that systematic diagnosis and replacement of damaged components restored the tested body electrical functions.